Neurodegeneration and Neuroinflammation in Diabetic Retinopathy: Potential Approaches to Delay Neuronal Loss - KadŦ#130;ubowska, Joanna; Malaguarnera, Lucia; WĦ#133;ż, Piotr; Zorena, Katarzyna (Current Neuropharmacology, 2016)
In spite of the extensive research the complex pathogenesis of diabetic retinopathy (DR) has not been fully elucidated. For many years it has been thought that diabetic retinopathy manifests only with microangiopathic lesions, which are totally responsible for the loss of vision in diabetic patients. In view of the current knowledge on the microangiopathic changes in the fundus of the eye, diabetic retinopathy is perceived as a neurodegenerative disease. Several clinical tools are available to detect neuronal dysfunction at early stages of diabetes. Many functional changes in the retina can be identified before vascular pathology develops, suggesting that they result from a direct effect of diabetes on the neural retina. In the course of diabetes there is a chronic loss of retinal neurons due to increased frequency of apoptosis. The neuronal apoptosis begins very early in the course of diabetes. This observation has led to suggestions that precautions against DR should be implemented immediately after diabetes is diagnosed. Neurodegeneration cannot be reversed; therefore treatments preventing neuronal cell loss in the retina need to be developed to protect diabetic patients. This review is an attempt to summarize what is currently known about the mechanisms of neuronal apoptosis in the context of diabetic retinopathy and vascular degeneration as well as about potential treatments of DR.
Keywords: Diabetic retinopathy